BURNOUT AMONG PEDIATRIC TRAINEES IN INDONESIA: A NATIONAL SURVEY - Annang Giri Moelyo; Bambang Tridjaja; Rina Triasih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2021)
Background: The intense workload and complex learning environment in pediatric specialist training program may lead to trainees’ burnout. The study aimed to assess burnout and the associated factors among pediatric trainees in Indonesia.Methods: We conducted a multicentre study involving all (15) pediatric training institutions in Indonesia from June to August 2019. A General Oldenburg Burnout Inventory (OLBI) was translated to Indonesian language. The OLBI comprised of 16 questions which assessed exhaustion (8 questions) and disengagement (8 questions). The online questionnaire was self-completed by pediatric trainees in the study sites. Ordinal regressions were performed to assess risk factors (age, marital, sex, resident stage of training, and university) for exhaustion and disengagement.Results: A total of 841 trainees from 15 pediatric training institutions in Indonesia completed the survey (response rate 71.2%). The majority (72.1%) of the trainees was female with mean age of 31.2 ± 2.9 years. The Cronbach’s-alpha was 0.74. The mean exhaustion and disengagement scores were 2.58±0.23 and 2.51±0.23, respectively. The proportion of vigor, mild, moderate and severe exhaustion were 48.3%; 42.0%; 9.0%; and 0.7%, respectively. The proportion of dedicated, mild, moderate and severe disengagement were 36.9%; 46.5%; 14.5%; and 2.1%, respectively. The stage of training (junior-intermediate stage), after adjusted to age, sex and institution was significantly increase the risk for exhaustion [odd ratio 1.47 (95%CI; 1.22-1.76)]. Disengagement level was significantly different among pediatric training institutions (located in Java and outer Java) [odd ratio 0.68 (95%CI; 0.529-0.885)].Conclusion: Burnout was common among pediatric trainees in Indonesia.